God, The Creator Versus Man, The Explorer and Manipulator - Singh, Arambam Giridhari (Journal of Nobel Medical College, 2016)
On 26th December 2016, the author of this Editorial was changed from Sita Pokhrel TO Arambam Giridhari Singh Not available.